(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The training of people in Applied Behavior Analysis (ABA), through Behavioral Skills Training (BST), to intervene with children with Autism Spectrum Disorder (ASD) involves guidelines on target behaviors to be taught, modeling, behavioral rehearsal and feedback. The literature presents positive results in training several populations. This research assessed the effects on teaching verbal operants by six Psychology students in a research and intervention laboratory. They went through a mandatory observational internship involving behavioral intervention in children with ASD. During baseline, none of them demonstrated 90% accuracy. When BST training with immediate and delayed feedback were defined, this accuracy level was achieved by all of participants. Both baseline and training were conducted with a research assistant. After training, a generalization probe was conducted during the teaching of verbal operants to a child with ASD and all college students demonstrated 100% accuracy.